Global warming trends ecological footprints - Casper, Julie Kerr. (New York, NY : Facts on File, 2009)
Provides an introduction to global warming that explains why and how it occurs and the accuracy and inaccuracy of the media type that accompanies it.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Paleoclimatology; Global warming; Electronic books